2019
DOI: 10.1101/596569
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early Hippocampal Sharp-Wave Ripple Deficits Predict Later Learning and Memory Impairments in an Alzheimer’s Disease Mouse Model

Abstract: Alzheimer's disease (AD) is characterized by progressive memory loss, and there is a pressing need to identify early pathophysiological alterations that predict subsequent memory impairment.Hippocampal sharp-wave ripples (SWRs) -electrophysiological signatures of memory reactivation in the hippocampus -are a compelling candidate for doing so. Mouse models of AD show reductions in both SWR abundance and associated slow gamma (SG) power during aging, but these alterations have yet to be directly linked to memory… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Gabra2, GABA A receptor alpha subunit, is involved in generation of brain oscillations critical for cognition 61 . We found a highly significant and consistent downregulation of Gabra2, which could link APOE4 to known oscillatory disruptions 62,63 . Thus, our results support prior studies that have documented synaptic deficits in APOE4-KI mouse brains 32,33,35 and, importantly, associate these detrimental effects to neuronal APOE4.…”
Section: Discussionsupporting
confidence: 62%
“…Gabra2, GABA A receptor alpha subunit, is involved in generation of brain oscillations critical for cognition 61 . We found a highly significant and consistent downregulation of Gabra2, which could link APOE4 to known oscillatory disruptions 62,63 . Thus, our results support prior studies that have documented synaptic deficits in APOE4-KI mouse brains 32,33,35 and, importantly, associate these detrimental effects to neuronal APOE4.…”
Section: Discussionsupporting
confidence: 62%
“…Article ll OPEN ACCESS SWR rate predicts memory impairments in Alzheimer's models (Jones et al, 2019). However, we found that suppressing SST + interneurons also lengthened SWRs, which may increase the length of the underlying replay trajectory, which could facilitate learning in some cases (Ferna ´ndez-Ruiz et al, 2019).…”
Section: Discussionmentioning
confidence: 71%
“…SST + interneurons in the DG are specifically lost in Alzheimer's disease and normal aging models, and the extent of their loss correlates with memory impairments (Andrews-Zwilling et al, 2010;Leung et al, 2012;Spiegel et al, 2013). These models show reduced SWR rate, frequency, and coincident SG power (Cayzac et al, 2015;Ciupek et al, 2015;Cowen et al, 2018;Gillespie et al, 2016;Iaccarino et al, 2016;Nicole et al, 2016;Wiegand et al, 2016), and the extent of these impairments predicts memory deficits (Jones et al, 2019). Suppression of DG and CA3 SST + interneurons induces similar changes in SWR characteristics, serving as further evidence that loss of these interneurons may be directly responsible for SWR alterations in pathological and normal aging and related memory deficits.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mouse models of tauopathy and familial AD show changes in markers of memory replay. For example, the density and amplitude of hippocampal sharp wave ripples (SWRs) are reduced in these models [44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%